Carnival theater : Uruguay's popular performers and national culture - Remedi, Gustavo (Cultural studies of the Americas, 2004)
Focusing on the cultural practices of the lower classes and specifically on the productions of the murgas, Carnival Theater is a consideration of Uruguayan societys identity crisis and subsequent redefinition in the wake of the regimes of the 1970s. A revealing work of cultural criticism, the book proposes a new set of criteria for the critique of national culture.